Feeding behaviors of a sea urchin, Mesocentrotus nudus, on six common seaweeds from the east coast of Korea - Yang, Kwon Mo; Jeon, Byung Hee; Kim, Hyung Geun; Kim, Jeong Ha (Algae (Korean Phycological Society), 2021)
The sea urchin, Mesocentrotus nudus, is widely distributed in North West Pacific regions. It has a substantial impact on macroalgal communities as a generalist herbivore. This study examined various aspects of its feeding ecology, including algal preference, foraging behaviors, and possible effects of past feeding history on its algal preference. We used six common algal species (Ulva australis, Undaria pinnatifida, Sargassum confusum, Dictyopteris divaricata, Grateloupia elliptica, and Grateloupia angusta) from the east coast of Korea as food choice in a series of indoor aquarium experiments. The first choice of starved M. nudus was exclusively U. pinnatifida, followed by G. elliptica and S. confusum. Unlike large urchins, small urchins equally preferred U. pinnatifida and G. elliptica. On the other hand, Undaria-fed urchins preferred to feed only G. elliptica, although its preference slightly differed over time. We then grouped sea urchins into three categories (starved, Undaria-fed, mixed species-fed) to observe 12-days feeding preference as well as early foraging movements. Foraging behaviors of the three groups were distinctively different, although they could not completely reflect the actual consumption. For example, U. australis was highly attractive, but rarely eaten. Undaria-fed urchins seemed to stay with only S. confusum and U. australis. This study demonstrates that M. nudus shows high flexibility in food preference depending on past feeding history and body size. Its foraging behaviors are also affected by past feeding conditions, exhibiting active chemoreceptive movements.